EXPANDING ACADEMIC VOCABULARY WITH AN INTERACTIVE ON-LINE DATABASE - Marlise Horst; Tom Cobb; Ioana Nicholae (Language Learning and Technology)
University students used a set of existing and purpose-built on-line tools for vocabulary learning in an experimental ESL course. The resources included concordance, dictionary, cloze-builder, hypertext, and a database with interactive self-quizzing feature (all freely available at www.lextutor.ca). The vocabulary targeted for learning consisted of (a) Coxhead's (2000) Academic Word List, a list of items that occur frequently in university textbooks, and (b) unfamiliar words students had met in academic texts and selected for entry into the class database. The suite of tools were designed to foster retention by engaging learners in deep processing, an aspect that is often described as missing in computer exercises for vocabulary learning. Database entries were examined to determine whether context sentences supported word meanings adequately and whether entered words reflected the unavailability of cognates in the various first languages of the participants. Pre- and post-treatment performance on tests of knowledge of words targeted for learning in the course were compared to establish learning gains. Regression analyses investigated connections between use of specific computer tools and gains.